2007
DOI: 10.1159/000100873
|View full text |Cite
|
Sign up to set email alerts
|

rhGH Treatment in Corticosteroid-Treated Patients

Abstract: Children and adolescents treated for chronic diseases have non-specific metabolic abnormalities that lead to decreased growth velocity and abnormal body composition, including severe osteoporosis, muscle wasting and increased fat mass. Glucocorticoid (GC) therapy plays a major role in the complex pathogenesis of these metabolic abnormalities. Recombinant human growth hormone (rhGH) therapy was introduced a few years ago to reduce the severe disease- and GC-related metabolic consequences of juvenile idiopathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…Long-term steriod-induced growth retardation may be due to a combination of factors such as a disruption of the growth hormone insulin-like growth factor-I axis, a defect in sex steroid action, a disturbance in calcium and phosphate homeostasis as well as direct effects on the growth plate (9). Long-term corticosteroid treatment alters the pulsatility and secretion of growth hormone by increasing the somatostatin inhibitor tone (10). Chronic steroid prescription also reduces the expression of growth hormone receptors in hepatocytes, leading to lower mRNA levels of Insulin-like growth factor-1 in the liver (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term steriod-induced growth retardation may be due to a combination of factors such as a disruption of the growth hormone insulin-like growth factor-I axis, a defect in sex steroid action, a disturbance in calcium and phosphate homeostasis as well as direct effects on the growth plate (9). Long-term corticosteroid treatment alters the pulsatility and secretion of growth hormone by increasing the somatostatin inhibitor tone (10). Chronic steroid prescription also reduces the expression of growth hormone receptors in hepatocytes, leading to lower mRNA levels of Insulin-like growth factor-1 in the liver (11).…”
Section: Discussionmentioning
confidence: 99%
“…Early administration of growth hormone therapy in long-term steriod treated patients might be a better strategy (10). European and US clinical studies showed that rhGH treatment was effective and safe improving height standard deviation score in prepubertal and pubertal children (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…A few years ago short-and mid-term recombinant human growth hormone (rhGH) therapy was introduced to reduce the Treatment of osteoporosis in children with GC-treated diseases Review informahealthcare.com metabolic consequences related to GC treatment in juvenile idiopathic arthritis, other chronic diseases and renal transplantation [71] rhGH treatment has been consistently proved to be effective in overcoming GC-induced growth suppression, with a marked interindividual variability. Safety of rhGH treatment, concerning the progression of the disease and glucose tolerance, was good.…”
Section: Recombinant Human Growth Hormonementioning
confidence: 99%
“…Vitamin D/calcium [42][43][44][45][46][47] Not recommended therapies Bisphosphonates [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] New therapies Teriparatide [64][65][66][67][68][69][70] GnRh [71] GnRh + oxandrolone [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] Denosumab [90] Anti-DKK1 [91] Anti-sclerostin [94,95] Romosozumab [93]…”
Section: Recommended Therapiesmentioning
confidence: 99%
“…This acceleration in linear growth was associated with significant increases in serum levels of IGF-I and IGF-binding protein-3 (IGFBP-3), which persisted as long as GH therapy was continued [9] and indicated a preserved sensitivity to GH. However, in contrast to data obtained with GH use in other indications, catch-up growth did not occur consistently; there is marked interindividual variability [12]. Continued GH replacement for up to 3 years halted the statural loss usually seen during the active phase of JIA and kept patients on the growth curve that corresponded to their height at treatment initiation [10].…”
Section: Trials Of Gh Therapy: Effects On Growthmentioning
confidence: 99%